Analysis of a Feder - Rádi Ferenc (Bern Open Publishing, 2014)
This paper covers an analysis in the cross section of sword fencing and the field of analytical mechanics and computer analysis. It aims to get answer to following questions in case of a normal blow with a feder on another feder: where are critical cross section/sections, where is the biggest stress, might the feder maybe break or not?